Respuesta :
Answer:
Infinitely many solutions.
Step-by-step explanation:
2 (n - 1) + 4n = 2 (3n - 1) Let's simplify this to solve it.
2n - 2 + 4n = 6n - 2 Distribute 2(n-1) and 2(3n-1)
2n + 4n - 2 = 6n - 2 Rearrange the left side of the equation.
6n - 2 = 6n - 2 Add 2n + 4n.
-6n -6n Subtract 6n from both sides.
-2 = -2? Yes, -2 equals -2.
Therefore, the answer is infinitely many solutions, meaning that n can be any real number.
An equation can have no solution, one solution or infinitely many solutions.
The equation [tex]2(n -1) + 4n = 2(3n - 1)[/tex] has infinitely many solutions
Given that:
[tex]2(n -1) + 4n = 2(3n - 1)[/tex]
Open brackets
[tex]2n -2 + 4n = 6n - 2[/tex]
Collect like terms
[tex]2n + 4n - 6n= - 2+2[/tex]
[tex]0 = 0[/tex]
When the solution to an equation is 0 on both sides, the equation has infinitely many solutions
Read more about number of solutions at:
https://brainly.com/question/15272411